2017
DOI: 10.1111/jocs.13181
|View full text |Cite
|
Sign up to set email alerts
|

Long-term endothelial dysfunction after trans-radial catheterization: A meta-analytic approach

Abstract: Transradial catheterization impairs endothelium dependent vasodilatory properties of the cannulated RA, which do not recover even several months post-catheterization. Non-recovery of vasomotor function of cannulated RAs may limit their use as arterial grafts during CABG surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Pseudoaneurysm is an extremely rare complication in the RA approach (more common in transfemoral procedures) and occurs when an artery wall is injured, resulting in possible haemorrhage and haematoma in the surrounding tissue [11,26] . RA cannulation can also cause direct damage to the endothelium, which can affect RA function [38,39] impairing endotheliumdependent vasodilatory, anti-thrombotic and anti-mitogenic properties.…”
Section: Other Complicationsmentioning
confidence: 99%
“…Pseudoaneurysm is an extremely rare complication in the RA approach (more common in transfemoral procedures) and occurs when an artery wall is injured, resulting in possible haemorrhage and haematoma in the surrounding tissue [11,26] . RA cannulation can also cause direct damage to the endothelium, which can affect RA function [38,39] impairing endotheliumdependent vasodilatory, anti-thrombotic and anti-mitogenic properties.…”
Section: Other Complicationsmentioning
confidence: 99%
“…Finally, surgeons should know whether the RA that is to be harvested has been recently cannulated during a diagnostic cardiac catheterization. There is evidence to suggest that transradial catheterization results in endothelial vasomotor dysfunction that may last for several months and could adversely affect graft patency . Caution should be exercised when considering the use of these conduits for CABG …”
Section: Resultsmentioning
confidence: 99%
“…Concerns were also raised regarding the use of the RA following trans radial artery access for diagnostic or interventional procedures. In a meta‐analysis involving patients undergoing cardiac catheterization using the RA, Antonopoulus et al found that trans radial artery catheterization impaired endothelium‐dependent vasodilation of the RA and this persisted even after 3 months . This has raised concerns that surgeons should avoid using the RA as coronary grafts following any instrumentation including its cannulation in arterial blood pressure monitoring .…”
Section: Ra Harvesting Techniques and Ra Use As A Coronary Graft Follmentioning
confidence: 99%